2021
DOI: 10.30827/digibug.70277
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link between Athletic Identity, Self-compassion, Communication, and Mental Toughness of Table Tennis Student- Athletes

Abstract: Exploración del vínculo entre identidad deportiva, autocompasión, comunicación y fortaleza mental de los estudiantes-atletas de tenis de mesa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Their results suggested that mental toughness and self-compassion were indeed compatible, complementary concepts ( Wilson et al, 2019 ; Johnson, 2020 ; Stamatis et al, 2020 ; Maranan and Lopez, 2021 ). Self-compassion helped performers cope with difficult situations, whereas mental toughness seemed to be helpful in maintaining high motivation, concentration, and resilience ( Wilson et al, 2019 ; Stamatis et al, 2020 ).…”
Section: Data Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…Their results suggested that mental toughness and self-compassion were indeed compatible, complementary concepts ( Wilson et al, 2019 ; Johnson, 2020 ; Stamatis et al, 2020 ; Maranan and Lopez, 2021 ). Self-compassion helped performers cope with difficult situations, whereas mental toughness seemed to be helpful in maintaining high motivation, concentration, and resilience ( Wilson et al, 2019 ; Stamatis et al, 2020 ).…”
Section: Data Synthesismentioning
confidence: 99%
“…Can mental toughness and inner kindness toward oneself work together to support mental health and performance? Despite differences, it seems that mental toughness and self-compassion share many commonalities ( Wilson et al, 2019 ; Johnson, 2020 ; Stamatis et al, 2020 ; Maranan and Lopez, 2021 ). To the best of our knowledge, Wilson et al (2019) were the first to explore the compatibility of these two concepts with regards to athletic performance.…”
Section: Data Synthesismentioning
confidence: 99%
See 3 more Smart Citations